Determinants of Increased Transmitral Gradients Under Dynamic Isometric Handgrip Exercise After Edge-to-Edge Repair With the Fourth-Generation MitraClip - Giuseppe D’Ancona; Antonia Anna Ourani; Evangelos Chaidos; Catherine Louise Steinbach; Hüseyin Ince; Raid Al Ammareen (Journal of Interventional Cardiology)
Conclusion: Wide MitraClips effectively reduce MR with satisfactory haemodynamic performance. Handgrip stress echocardiography is a feasible and valuable tool for assessing postprocedure valve function. Larger cohorts are necessary to confirm the impact of secondary MR and use of multiple clips on increased TMG under stress.